Os significados entre residentes de enfermagem obstétrica sobre o processo de ensino-aprendizagem no campo de prática assistencial - MOURA, Letícia Diogo de Oliveira (Universidade Federal do Pará, 2023)
The teaching learning process in Obstetric nursing education seeks to include technical recommendations that significantly contribute to the transformation of the obstetric care scenario. Understanding the importance of the teaching-learning process in the qualification of new professionals is part of the transformation of this scenario. Object of study: the meanings amongst residents about the teaching-learning process in the practice scenarios of the Residency Program in Obstetric Nursing. Guiding question: What are the meanings amongst residents about the teaching-learning process carried out in the practice scenario of obstetric nursing? General objective: to analyze the meanings amongst residents about the teaching-learning process in the practice scenarios of the Residency Program in Obstetric Nursing. Specific objectives: to describe the teaching-learning process experience with residents in obstetric nursing; to discuss the possible obstacles in the practice scenario that impact the teaching-learning process. Methodology: a qualitative case study approach. The research was carried out in the obstetric nursing residency program at the Institute of Health Sciences of the Federal University of Pará. The research participants were twenty-two residents of the 1st and 2nd year of the program, which followed the intentional recruitment and application of the following inclusion criteria: being regularly enrolled as residents; have spent at least 1 month at the UBS, hospital and management level. The following exclusion criteria were established: residents on maternity leave or due to illness; residents who dropped out of the program. Data collection was carried out through four focus groups with both classes, being three groups with six residents and one group with 4 residents, obtaining two refusals to participate. The groups had two face-to-face meetings and an average lenght of 120 minutes. A conceptual map on positive and negative aspects of the residence was also used. Audio recording was used, which was transcribed in full with the information. The study was approved by the Research Ethics Committee of the Institute of Health Sciences of the Federal University of Pará, under No. 5.443.574/2022. The data were submitted to content analysis in the thematic modality with organization support of the ATLAS.ti 22.7 software, with the realization of the following codes: Preceptorship; resident R2; residency reception; the residency course in obstetric nursing. The results showed that preceptorship is a facilitating and integrating link in learning, with many professional references focused on training new qualified obstetric nurses. But also, the need of reception, empathy, involvement and integration in the training of preceptorship and with scientific evidence, aligned with theory and practice. Also, the extension of investment in preceptorship as a foundation to grant better formation. However, the second-year resident constitutes an important strategy for the aggregation of preceptorship with the firstyear residents, with their reception and conflict mediation. However, the lack of a sense of belonging and the management organization are important senses that must be worked along with the course and the practice scenario. It is concluded that this study achieved its initial objectives, elucidating the meanings of residents in obstetric nursing about the learning teaching process and provided support for future changes to be thought and carried out in the training of new obstetric professionals.